A New Cell Formation Method Considering Operation Sequences And Production Volumes - Abedini, Panteha (2013)
In today’s market, customers are demanding more customized products. Hence, manufacturing companies are forced to produce a variety of products with various options and features in small batches. Under such circumstance, frequent changes take places in product design, product mix, product volume and production process affecting the manufacturing layout. To fulfill these requirements and respond to the changes, companies need to adopt appropriate shop floor layout to improve their operations in terms of higher productivity, better quality and customer responsiveness. Cellular layout is an alternative layout and is suitable for manufacturing companies which are characterized by low volume and high product variety. Cellular layout is composed of cells that ideally act as independent entities. Also, each cell is composed of a group of machines that can process a family of parts. Identification of machines and parts in each cell, known as cell formation, is the core and critical step component of cellular layout. This research, presents an algorithm for cell formation to minimize intercellular movements. The algorithm considers two production factors, operation sequences and production volumes of each part as well as the number of cells can be identified in advance. The graph theory was employed to develop the algorithm. It consists of four stages that the first one shows the sequences of machines that are used by each part in a graph. The second stage calculate the relationships between machines based on the production volume of each part (calculate the weight of each edge of the graph).